Coping Stress among Students during Undergraduate Research Project - Prahastia Kurnia Putri (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2021)
To Finish undergraduate degree, college students have to complete their final task, undergraduate thesis. Working on Undergraduate thesis could be a stressor since this is unstructured activity in college unlike regular class. They are demanded to finish their study on time, maintain relationship with supervisor, thesis content and writing, are such conditions that come along during thesis project. Based on those phenomena, research of this study is aimed to understand and describe coping stress on College Students to reduce their stressor during thesis project. This research is using Coping Stress theory based on Lazarus & Folkman (1984) that consists of Problem Focused-Coping and Emotion-Focused Coping. This research using quantitative method with descriptive statistics to describe Coping Stress’s dimension: Problem-Focused Coping and Emotion Focused Coping to College Students who finishing undergraduate thesis. Sample in this study is 63 college students with convenient sampling technique. Coping Stress was measured by Coping Stress Questionnaire modified by Muchlisin & Putri (2018) based on Coping Stress Questionnaire by Lazarus & Folkman (1984). This questionnaire was made for college students and thesis project context. Findings of this study is most of college students show low level of Coping Stress. And Coping strategy most used is Problem-focused coping.